2020
DOI: 10.2139/ssrn.3624264
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Before and During the COVID-19 Pandemic: A Longitudinal Probability Sample Survey of the UK Population

Abstract: Mental health before and during the COVID-19 pandemic: a longitudinal probability sample survey of the UK population

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

61
585
9
16

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 421 publications
(671 citation statements)
references
References 11 publications
61
585
9
16
Order By: Relevance
“…Our measurements showed that COVID-19 lockdown resulted in a significant 1.4-and 5.5-fold increase in stress levels and depressive symptoms, respectively. The observed increase in stress levels and severity of depressive symptoms is consistent with reported cross-sectional (26,46,47) and longitudinal (15,17,19) general population studies. In agreement with previous reports (48,49), we found a more pronounced impact of the COVID-19 lockdown on the mental health of women.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our measurements showed that COVID-19 lockdown resulted in a significant 1.4-and 5.5-fold increase in stress levels and depressive symptoms, respectively. The observed increase in stress levels and severity of depressive symptoms is consistent with reported cross-sectional (26,46,47) and longitudinal (15,17,19) general population studies. In agreement with previous reports (48,49), we found a more pronounced impact of the COVID-19 lockdown on the mental health of women.…”
Section: Discussionsupporting
confidence: 90%
“…Our study has also its limitations. First, the population sample is rather small compared to some recently reported studies (17,19,65). Second, only 40% of the participants of the Kardiovize study accepted the electronic invitation to participate in the COVID-19 add-on study.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The temporal differences in anxiety levels between lockdown and post lockdown might indicate a need for well-being intervention programs and a focus on designing health awareness messages that do not raise anxiety to the degree that could increase the burden of poor mental health associated with the pandemic worldwide (38,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%